High-yield hydrogen production via dolomite/ilmenite synergistic catalytic gasification in a fluidized bed reactor - Shaosheng Fang; Panting Li; Dongfang Li; Shaoxiang Pu; Rong Yang; Aoyang Zhang; Xing Zhu; Hairui Yang; Man Zhang; Hua Wang (Fuel, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Field measurements of the structural response of a linked twin-tower super-tall building during two typhoons - Liang Han; An Xu; Jiyang Fu; Yangxue Wang; Hua Rong; Wei Shi; Lele Zhang (Engineering Structures, 2026)

Conjugation-enhanced crown ether-based polymer for “locking-controlled” recognition and confined space synergistic co-capture of Sr(II) and U(VI) - Qi-Dong Ye; Jie Wang; Yang Li; Yang Wang; Zi-Hao Feng; Dong-Qing Huang; Yun Wang; Shuang Yang; Rong Hua (Desalination, 2026)

The Importance of Subsurface Thermal Effects to Indian Ocean Dipole Prediction Revealed by a Skillful Three-Dimensional Deep Learning Model - Junkai Qian; Qiang Wang; Youmin Tang; Rong-Hua Zhang; Henk A. Dijkstra; Yoo-Geun Ham; Wansuo Duan; Xiangzhou Song; Gang Huang; Suqi Peng (Advances in Atmospheric Sciences, 2026)

The Study on the Biological Characteristics of Photobacterium damselae subsp. damselae Affected by the Deletion of the Iron Uptake System Genes tonB1 and tonB2 - Hua Jiang; Yufei Ji; Zhiqi Zhang; Yongxiang Yu; Chunyuan Wang; Yingeng Wang; Xiaojun Rong; Aijun Ma; Shuyi Li; Zheng Zhang (Fishes, 2026)
Photobacterium damselae subsp. damselae (PDD), a marine fish pathogen, has an unclear contribution of tonB genes to iron acquisition and pathogenicity. ΔtonB1-PDD and ΔtonB2-PDD mutants as well as their complemented strains were generated via homologous recombination from the virulent strain PDD1605. Growth was evaluated by monitoring OD600 with viable-count calibration, intracellular iron was measured using a colorimetric assay, biofilm was detected by crystal violet staining, transcription was analyzed through qRT-PCR, and pathogenicity was assessed via an 8-day intramuscular challenge in black rockfish (Sebastes schlegelii). Under iron limitation induced by 100 μM 2,2′-dipyridyl, the maximum density decreased from 4.51 × 108 CFU/mL in wild-type (WT-PDD) to 4.00 × 108 and 3.64 × 108 CFU/mL in ΔtonB1-PDD and ΔtonB2-PDD respectively, and was largely restored after complementation. The intracellular iron content declined from 3.75 × 10−4 ± 4.00 × 10−6 nmol/106 cells in WT-PDD to 3.13 × 10−4 ± 1.05 × 10−5 nmol/106 cells in ΔtonB1-PDD and 2.55 × 10−4 ± 2.00 × 10−5 nmol/106 cells in ΔtonB2-PDD. Compared with WT-PDD, biofilm formation was reduced by 22.1% in ΔtonB1-PDD and by 24.8% in ΔtonB2-PDD. Deletion of tonB2 induced mild yet statistically significant transcriptional alterations in multiple iron acquisition and virulence-related genes, while colony morphology, swarming motility, hemolysis, phospholipase activity, biochemical traits, and antimicrobial susceptibility remained unchanged. In the high-dose challenge assay, WT-PDD caused 100% mortality within 2 days, whereas ΔtonB1-PDD and ΔtonB2-PDD caused 17/20 and 18/20 deaths respectively; all infected groups reached 100% mortality by day 3. In the low-dose challenge assay, WT-PDD, ΔtonB1-PDD, and ΔtonB2-PDD caused 12/20, 12/20, and 13/20 deaths by day 2, with cumulative mortalities reaching 80%, 70%, and 80% by day 8, respectively. Kaplan–Meier analysis detected no significant differences among the survival curves at either challenge dose. These findings suggest that tonB1 and tonB2 play roles in iron acquisition, low-iron adaptation, and biofilm formation, with tonB2 deletion exerting greater effects on growth and intracellular iron accumulation under iron-limited conditions.

Assessing impacts of vertical mixing parameterizations on ENSO simulation in a ROMS-based hybrid coupled model - Yinnan Li; Yang Yu; Maonan Chen; Chuan Gao; Hongna Wang; Liu Yang; Rong-Hua Zhang (Journal of Oceanology and Limnology, 2026)

Oxygen mass transfer characteristics of different hollow-fiber bubble-free aeration membranes via clean water oxygenation tests under different aeration and measurement modes - Zhe Yuan; Chun-Hai Wei; Jing-Su Liu; Zhi-Wei Lian; Jing-Yin Wang; Hua-Rong Yu; Hong-Wei Rong; Zhi-Hui Pan; Zhong-Lin Nie; Ya-Song Chen; Xia Huang (Water Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

8-epi-11-oxotanzawaic acid A, an undescribed tanzawaic acid analog from the marine fungus Penicillium citreonigrum - Ze-Qing Li; Rong Chao; Si-Yu Fang; Tian-Hua Zhong; Yuan Wang (Phytochemistry Letters, 2026)

Reaction-generated secondary phase advances electronic-phonon decoupling and boosted mechanical performance in Bi0.42Sb1.58Te3 alloys - Yi-lin Liu; Hao Liang; Chong-Yu Wang; Jiang-Hu Yu; Kang Yue; Qian Deng; Ju Rong; Jing Feng; Zhen-Hua Ge (Chemical Engineering Journal, 2026)

Histamine regulation in shaping spindle refractoriness: a computational modeling study - Bo Wang; Qiang Li; Wen-Hua Wang; Wan-Rong Zan; Yi-Ming Li; Jiang-Ling Song; Rui Zhang (Journal of Computational Neuroscience, 2026)

Unraveling the complex interplay between glymphatic function, age, and brain structure in school-aged children with autism spectrum disorder - Zhongfeng Xie; Di Zhou; Shuchao Wang; Ting Hua; Hong Chen; Rong Yang; Yujiao Gong; Guangyu Tang; Lin Zhang; Xiaowen Xu (Brain Imaging and Behavior, 2026)

Integrated metabolomic and transcriptomic analyses reveal that pectin metabolism mediates texture divergence in grape berries - Zhi-Meng Gan; Xiao-Yan Ai; Yong Liu; Wei Zhu; Yang Zhang; Hui-Liang Wang; Fu-Rong Wang; Xiao-Dong Hou; Hua-Ping He; Lin-Zhong Gong (Postharvest Biology and Technology, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Changes in flavor profiles and microbial community diversity throughout rice wine fermentation with Rhizopus oryzae from different sources - Ting Tong; Jing-Rong Hu; Zhen-Jia Li; Zi-Zhen Qin; Cai-Hua Shi; Han-Cheng Wang (International Journal of Food Microbiology, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Boosting char formation in lignin aerogels via PN synergy: A route to flame retardancy and multifunctional performance - Jia-Hui Wang; Tao Gui; Shuang-Lin Zou; Qing-Hua Wang; Ying-Chun Xu; Rong Tan; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Chemical Engineering Journal, 2026)

Advances in the regulation of NLRP3 inflammasome by natural polysaccharides: Structural features, mechanisms of action, and disease associations - Xuebin Xu; Rong Ji; Hua Huang; Jiufu Xiao; Han Zhang; Haixue Kuang; Zhibin Wang (Carbohydrate Polymers, 2026)

Characteristics of summer typhoon activities over China during 2020–2022 and their relationships with the Triple La Niña events - Qing-Bo Zeng; Ying Wang; Rong-Hua Zhang (Atmospheric Research, 2026)

Optimization of pediatric dosing regimens for aztreonam and amoxicillin/clavulanate combination therapy against multidrug-resistant bacteria - Lili Wang; Mengyuan Wu; Lin Qu; Pengfei Wang; Ziwei Yu; Hua Deng; Frederico S. Martins; Jiayuan Zhang; Da Rong; Mingming Yu; Zhihua Lv; Sherwin K. B. Sy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Chemical constituents and ferroptosis inhibitory activity of the deep-sea-derived fungus Penicillium citrinum W24 - Cheng-You Lin; Yuan Wang; Tai-Zong Wu; Rong Chao; Zheng-Biao Zou; Li-Sheng Li; Tian-Hua Zhong; Xian-Wen Yang (Natural Product Research, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

Human MAITregs possess diverse TCR repertoires and are functionally supported by glycolysis - Maoyu Tang; Xinying Li; Xudong Yang; Changfeng Zhao; Yuwei Zhang; Sanwei Chen; Zhenghui Ye; Liujin Hou; Yusheng Chen; Rong Lv; Hongchuan Zhao; Xiaowen Cheng; et al. (Science China Life Sciences, 2026)

Rapid retreat of the East Asian summer monsoon at the end of the Holocene humid period accelerated the transition from broadleaf to pine forest landscapes in northern China - Linjing Liu; Xin Mao; Lei Song; Xingqi Liu; Dejun Wan; Gaolei Jiang; Jingsong Yang; Hongmei Zhao; Chengmin Wang; Hua Zhao; Rong Ma (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

Chronic heat stress attenuates innate immunity and increases susceptibility to Aeromonas hydrophila in Siberian sturgeon (Acipenser baerii) - Xiaowen Wang; Huijuan Li; Rong Zhang; Lili Liu; Wei Wang; Hua Zhu (Aquaculture International, 2026)

Applying semi-supervised learning algorithms in real-environment solid waste classification - Dong–Ying Lan; Pin–Jing He; Hui–Huang Zou; Rong–Rong Kan; Yi Wang; Fan Lü; Hua Zhang (Resources, Conservation and Recycling, 2026)

Tropical instability waves and their relationships with large-scale oceanic thermal conditions, revealed in ROMS-based hybrid coupled model of the tropical Pacific - Yinnan Li; Yang Yu; Chuan Gao; Hongna Wang; Rong-Hua Zhang (Journal of Oceanology and Limnology, 2026)

Failure Behavior and Energy Evolution of Granite Containing Pre-existing Fissures Characterized by AE and DIC - Run-ze Zhang; Chuan-xin Rong; Bin Wang; Hua-qiao Xu; Yan-zhe Li; Yang Wang (Applied Geophysics, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Impacts of iron additives on enzymatic activities and nitrogen cycling during composting: Microbial and biochemical insights - Yang Wang; Hong-Yi Wu; Shuang-Yan Jia; Hao-Duo Bai; Kuok Ho Daniel Tang; Xiu-Na Ren; Zhixin Zhang; Yao Yiqing; Guo Xiaohui; Chugang Mei; Rong-Hua Li (Journal of Cleaner Production, 2026)

Dual efficient X-ray scintillation and strong second harmonic generation in a single cubic alkane Cu4I4 cluster achieved through organic-inorganic synergistic effect - Bao-Yi Li; Jun-Zhe Li; Wen-Fei Wang; Peng-Kun Wang; Rong Li; Shuai-Hua Wang; Fa-Kun Zheng; Guo-Cong Guo (Chemical Engineering Journal, 2026)

Advances in natural products with anti-skin photoaging: mechanisms, phytochemical diversity, and therapeutic potential - Yi Luo; Xiao-Cui Liu; Yu-Jie Li; Yu-Jia Wang; Ming-Hua Qiu; Xing-Rong Peng (Phytochemistry Reviews, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Chemical constituents from the heartwood of Pterocarpus erinaceus Poir and their chemotaxonomic significance - Zhong-Qi Lei; Xing Dai; Meng-Fei Wang; Lan-Ying Chen; Rong-Hua Liu (Biochemical Systematics and Ecology, 2026)

Quercetin Alleviates Postoperative Cognitive Dysfunction of Aged Mice by Regulating Microglial Polarization through Inducing miR-379-5p RNA Modification - Shu Rong Li; Long Wang; Yi Wei Li; Yi Xiao Li; Ren Wei Li; Zhi Fang Zhuo; Qing Hua Wu (Molecular Neurobiology, 2026)

Controls over soil water-extractable organic matter quantity and biodegradability in alpine coniferous forests of Southwest China - Le-Lin Yu; Qi-Tong Wang; Hua-Jun Yin; Rong Mao (European Journal of Forest Research, 2025)

Electrochemical and photoelectrochemical CO2 reduction to hydrocarbons by a copper-based molecular catalyst - Zhibing Wen; Rong Zhang; Yong Zhu; Hua Gao; Ran Zhao; Zhi Chen; Siyao Wang; Shuanglin He; Ya-Qiong Zhang; Rong-Zhen Liao; Fei Li (Chemical Engineering Journal, 2025)

Non-linear and contrasting responses of abundant, intermediate and rare prokaryotic phylotypes to environmental gradients in forests of East China - Guangxin Wang; Shuhan Zhang; Bin Hua; Rong Mao; Yang Zhang; Anton A. Goncharov; Ximei Zhang; Xingguo Han; Wei Yang (Applied Soil Ecology, 2025)

A preliminary study on the application of scale removal agents in neutral in-situ leaching for unblocking in sandstone-type uranium deposits - Yuxin Chen; Yichen Wu; Yuke Wang; Cong Huang; Xuebin Su; Rong Hua (Journal of Environmental Chemical Engineering, 2025)

Mechanical performance analysis of fully grouted bolts considering yield and hardening characteristics - Akang Li; Hua Cheng; Zhongwen Yue; Chuanxin Rong; Peng Wang; Jian Lin (International Journal of Rock Mechanics and Mining Sciences, 2025)

Adipose-bone microenvironment precision-regulation nanoplatform: A visualized mild photothermal-enhanced osteogenesis strategy for osteonecrosis of the femoral head - Jinxuan Li; Mengting Gao; Yuhang Wang; Rong Dai; Qi Liu; Shutong Wu; Jian Zhang; Hua Wu; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2025)

Hydro-mechanical and homogenization behaviour of GMZ bentonite pellets/block assemblies upon hydration - Zhang-Rong Liu; Wei-Min Ye; He-Hua Zhu; Yong-Gui Chen; Qiong Wang (Geomechanics for Energy and the Environment, 2025)

Rosmarinic acid in Perilla frutescens L. as a potential adenosine deaminase inhibitor: Preparation, machine learning validation and binding mechanism study - Bo-hao Liu; Zhong-Han Li; Bao-rong Wang; Jie Zhou; Bing Zhang; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Distinct mechanisms of marine heatwave formation in offshore waters of China - Zhibo Chen; Ying Wang; Jiaqi Wang; Rong-Hua Zhang; Yifan Jiang; Yu Qi; Xinchi Yu (Journal of Oceanology and Limnology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Mechanisms of integrated porous biochar and Fe3O4 in modulating carbon emissions and humification in co-composting of cattle manure and wheat stalk - Xu Yang; Cong Shao; Miaoqu Wang; Wanqiang Zhang; Wenxin Zhang; Haoduo Bai; Jie Zhang; Cleophas Achisa Mecha; Rong-Hua Li (Chemical Engineering Journal, 2025)

Ferritinophagy-derived iron causes protein nitration and mitochondrial dysfunction in acetaminophen-induced liver injury - Shi-Min Liang; Jie Shen; Rui-Ting Ma; Nan-Di Du; Rui Wang; Zuo-Min Wu; Min Shan; Shi-Rong Liang; Wei-Rong Hu; Wei Wang; Wei-Wei Sheng; De-Feng Huang; et al. (Toxicology and Applied Pharmacology, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

A soil–water retention model with differentiated adsorptive and capillary regimes - Zhang-Rong Liu; Wei-Min Ye; Yu-Jun Cui; He-Hua Zhu; Yong-Gui Chen; Qiong Wang (Computers and Geotechnics, 2025)

Fine mapping and functional validation reveal two incomplete dominant genes controlling photoperiod-sensitive flowering in Gossypium hirsutum - Langjing Hua; Chao Xu; Xiao Liu; Zhicheng Wang; Tengyu Li; Yuefen Cao; Xin Hu; Yurong Jiang; Junkang Rong (Theoretical and Applied Genetics, 2025)

A hybrid coupled model for the tropical Pacific constructed by integrating ROMS with a statistical atmospheric model - Rong-Hua Zhang; Wenzhe Zhang; Yang Yu; Yinnan Li; Feng Tian; Chuan Gao; Hongna Wang (Journal of Oceanology and Limnology, 2025)

Partitioning of evapotranspiration in semi-arid rain-fed farmland using an improved stomatal conductance model - Yongzhi Bao; Tingxi Liu; Limin Duan; Xin Tong; Yixuan Wang; Lina Hao; Rong Hua; V. P. Singh (Irrigation Science, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Extraction of hydroxy safflower yellow A and anhydroxysafflor yellow B from safflower florets using natural deep eutectic solvents: Optimization, biological activity and molecular docking - Chun-Ying Wu; Bao-Rong Wang; Si-Yi Han; Ying-Hua Zhang; Zhi-Shen Mu (Food Bioscience, 2025)

Improved rainfall infiltration model for probabilistic slope stability assessment considering transition layers and spatial variability - Shui-Hua Jiang; Zhi-Rong Yuan; Ze Zhou Wang; Xian Liu (Engineering Geology, 2025)

Integrating straw return and tillage practices to enhance soil organic carbon sequestration in wheat–maize rotation systems in the North China Plain - Hua Han; Daijia Fan; Shuxia Liu; Rong Jiang; Daping Song; Guoyuan Zou; Ping He; Minyu Wang; Wentian He (Agriculture, Ecosystems & Environment, 2025)

Aloe gel polysaccharides and ascorbic acid promote collagen synthesis in mirror carp (Cyprinus carpio var. specularis) - Rong Zhang; Xiaowen Wang; Lili Liu; Huijuan Li; Hua Zhu (Aquaculture, 2025)

Variation in climate and hydrological conditions in Southwest China during the mid-to-late Holocene, inferred from stalagmite multiple proxies - Hua-Yan Li; Yao Wu; Ting-Yong Li; Rong Duan; Hai-Bo Wang; Jia-Hui Cui; Chao-Jun Chen; Yue Jin; Yue-Hua Xiang; Zi-Qi Liu; Jun-Yun Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Isolation and genomic characterization of multi-drug resistant Morganella morganii strain from Chinese Soft-Shell Turtle Pelodiscus sinensis - Rong-Hua Wang; Meng-Lu Yan; Qing Tan; Jin-Long Wang; Yu-Shuang Luo; Zhong-Yuan Chen (Aquaculture, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Effects of triclosan on microalgal-bacterial symbiosis system operating in stable phase: Performances and mechanisms - Qiang Chao; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian (Journal of Water Process Engineering, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

α-asarone activates mitophagy to relieve diabetic encephalopathy via inhibiting apoptosis and oxidative stress - Xiao-dan Yan; Rong-hua Fan; Yu Wang; Xiao-xu Duan; Xuan Wei; Lin-sen Li; Qing Yu (Metabolic Brain Disease, 2025)

A plant growth-promoting bacterium supports cadmium detoxification of rice by inducing phenylpropanoid and flavonoid biosynthesis - Yingjie Wu; Haiyang Zhao; Meijuan Xiao; Huimin Liu; Hua He; Lu Peng; Qi Tao; Xiaoyan Tang; Yanyan Zhang; Rong Huang; Bing Li; Changquan Wang (Journal of Hazardous Materials, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

CSF multi-omics of intracerebral hemorrhage from onset to reperfusion underscores lipid metabolism in functional outcome - Yibin Jiang; Sin Man Lam; Shuixian Zhang; Huan Miao; Yong Zhou; Qian Zhang; Tengyuan Zhou; Hui Feng; Ning Ding; Haomiao Wang; Ran Luo; Yi Yin; et al. (Science Bulletin, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Meet-in-metabonomics: Insights into associations between hair heavy metal and adverse child growth in e-waste recycling area - Hong-Xuan Kuang; Meng-Yang Li; Jia-Rong Wang; Jian-Hua Tan; Wen-Yao Liang; Yang Zhou; Yun-Jiang Yu (Environmental Pollution, 2024)

Ultra-low temperature heating system based on dual-source solar assisted heat pump using compound parabolic concentrator-capillary tube solar collector - Li Wei Yang; Jin Huan Pu; Rong Ji Xu; Tong Yang; Hua Sheng Wang (Energy and Buildings, 2024)

p-Smad3 differentially regulates the cytological behavior of osteoclasts before and after osteoblasts maturation - Jiapeng Ye; Zhen Hua; Jirimutu Xiao; Yang Shao; Shaoshuo Li; Heng Yin; Mao Wu; Yi Rong; Bowen Hong; Yang Guo; Yong Ma; Jianwei Wang (Molecular Biology Reports, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Representing ocean biology-induced heating effects in ROMS-based simulations for the Indo-Pacific Ocean - Wenzhe Zhang; Chuan Gao; Feng Tian; Yang Yu; Hongna Wang; Rong-Hua Zhang (Frontiers in Marine Science, 2024)
Incident shortwave radiation can penetrate and heat the upper ocean water column, acting to modulate the stratification, vertical mixing and sea surface temperature. As a light-absorbing constituent, ocean chlorophyll (CHL) plays an important role in regulating these processes; however, its heating effect on the ocean state remains controversial and exhibits strong model dependence on ways the solar radiation transmission and the related CHL-induced heating are represented. In this study, we implement a chlorophyll-based two-way coupling between physical and ecological processes within the Regional Ocean Modeling System (ROMS). The bio-physics coupled model performs well in simulating the structure and variability of oceanic physical and ecological fields in the tropical Indo-Pacific region. Three CHL-related heating terms are analyzed based on the model output to diagnose the ocean biology-induced heating effects, namely the shortwave radiation part penetrating out of the base of the mixed layer (ML; Q pen ), the portion absorbed within the ML ( Q abs ), and the rate of temperature change of the ML resulting from the Q abs effects ( R sr ). Results show that the spatio-temporal distributions of the three heating terms are mainly determined by the ML depth (MLD). However, Q pen can also be regulated by the euphotic depth (ED), especially in the western-central equatorial Pacific. This moderating effect is particularly evident during El Niño when the ED tends to be greater than the MLD; positive ED anomalies act to enhance the positive Q pen anomalies caused by negative MLD anomalies. For the first time, the bio-heating effects are quantified within the ROMS-based two-way coupling context between the physical submodel and ecological submodel over the tropical Indo-Pacific Ocean, providing a basis for further understanding of the bio-effects and mechanisms. It is expected that the methodology and understanding developed in this study can help explore the chlorophyll-related processes in the ocean and the interactions with the atmosphere.

Dual isotope analysis reveals the COVID-19 lockdown impact on nitrate aerosol sources and formation pathways in Shanghai - Rong Wang; Hao Xiao; Yu Xu; Ai-Min Long; Min Zhou; Wen-Kai Guan; Hua-Yun Xiao; Hong-Wei Xiao (Science of The Total Environment, 2024)

PM2.5 constituents associated with mortality and kidney failure in childhood-onset lupus nephritis: A 19-year cohort study - Guohua He; Yaqi Wang; Cheng Cheng; Jianhui Guo; Zhilang Lin; Ziyun Liang; Bei Jin; Liyuan Tao; Liping Rong; Lizhi Chen; Tianxin Lin; Yining Hua; et al. (Science of The Total Environment, 2024)

Environmental high temperature affects pre-implantation embryo development by impairing the DNA repair ability - Si-Jing Qu; Shi-Yong Zhu; En-Yan Wang; Xin-Lei Yan; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2024)

Condensation heat transfer of zeotropic refrigerant mixtures R407C and R448A in a horizontal smooth tube - Yu Xia; Jian Yu; Dilara Suulker; Jin Huan Pu; Rong Ji Xu; Hua Sheng Wang (International Journal of Refrigeration, 2024)

Enhanced solar-driven steam generation and water purification using 3D arch solar evaporators - Yong-Gang Wu; Chao-Hua Xue; Xiao-Jing Guo; Meng-Chen Huang; Hui-Di Wang; Chao-Qun Ma; Li Wan; Shi-Qiang Lv; Wen-Min Zhang; Rong-Rong Gao (Desalination, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Numerical study on thermal–hydraulic behaviors of a natural circulation system with petal-shaped fuel rod bundle - Jian-Chuang Sun; Rong-Jiang Zhou; Xiang-Fei Meng; Jin-Yi Cao; Wen-Chao Zhang; Jin-Cheng Wang; Wei-Hua Cai (Annals of Nuclear Energy, 2024)

Cloning and functional identification of anthocyanin synthesis-regulating transcription factor AaMYB4 in Aeonium arboreum Webb & Berthel ‘Halloween’ - Rong Zhao; Su-Hua Li; Hao-Zhang Han; Li-Hua Zhang; Fang Wang; Nan Zhang (Brazilian Journal of Botany, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

Development of a method to assess synergy and competition for water use among water-energy-food nexus in the Yellow River basin: Water quantity-quality dimensions - Xinxueqi Han; En Hua; Jiajie Guan; Bernie A Engel; Rong Liu; Yawen Bai; Shikun Sun; Yubao Wang (Journal of Hydrology, 2024)

Development of an ELISA method to determine adulterated cow milk in camel milk - Shi-Xin Chi; Bo-Hao Liu; Bing Zhang; Bao-Rong Wang; Jie Zhou; Ling Li; Ying-Hua Zhang; Zhi-shen Mu (International Dairy Journal, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Identification of the Galactinol Synthase (GolS) Family in Medicago truncatula and Expression Analysis Under Abiotic Stress and Phytohormone Treatment - Hua Li; Ying Di Gao; Li Qing Kang; Hong Yang Yu; Li Ming Zeng; Yi Hua Wang; Rong Rong Chen; Jian Bo Song (Journal of Plant Growth Regulation, 2024)

Formation mechanism, environmental sensitivity and functional characteristics of succinylated ovalbumin/ε-polylysine electrostatic complexes: The roles of succinylation modification and ε-polylysine combination - Ru-yi Zhang; Hui-min Zhang; Tian-zhu Guan; Zhi-rong Wang; Hua-xiang Li; Lei Yuan; Yan-jun Yang; Sheng-qi Rao (Food Chemistry, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Salinity effect-induced ENSO amplitude modulation in association with the interdecadal Pacific Oscillation - Hai Zhi; Xiaokun Wang; Rong-Hua Zhang; Pengfei Lin; Jifeng Qi (Journal of Oceanology and Limnology, 2024)

Enhanced anaerobic digestion performance and sludge filterability by membrane microaeration for anaerobic membrane bioreactor application - Chun-Hai Wei; Zheng-Wei Wang; Jian-Hua Dai; Kang Xiao; Hua-Rong Yu; Fang-Shu Qu; Hong-Wei Rong; Jun-Guo He; Huu Hao Ngo (Bioresource Technology, 2024)

Expression analysis and antiviral activity of koi carp (Cyprinus carpio) viperin against carp edema virus (CEV) - Xiao-wen Wang; Rong Zhang; Li-li Liu; Hui-juan Li; Hua Zhu (Fish & Shellfish Immunology, 2024)

Different El Niño Flavors and Associated Atmospheric Teleconnections as Simulated in a Hybrid Coupled Model - Junya Hu; Hongna Wang; Chuan Gao; Rong-Hua Zhang (Advances in Atmospheric Sciences, 2024)

Generation of golden goldfish Carassius auratus via tyrosinase gene targeting by CRISPR/Cas9 - Huijuan Li; Xiaowen Wang; Rong Zhang; Lili Liu; Hua Zhu (Aquaculture, 2024)

Tsaokoflavanols A1–J1: Flavanol-fatty alcohol hybrids with HPL inhibitory activity from Amomum tsao-ko - Tian-Rong Yang; Shi-Chao Huang; Yun-Fen Wang; Zai-Xiang Lou; Shao-Xing Dai; Li-Hua Su; Min Xu (Phytochemistry, 2024)

Inactivation of antibiotic resistant bacteria by Fe3O4 @MoS2 activated persulfate and control of antibiotic resistance dissemination risk - Chang Rong; Haijun Chen; Zhuowen Wang; Shiyi Zhao; Deming Dong; Jiao Qu; Na Zheng; Haiyang Liu; Xiuyi Hua (Journal of Hazardous Materials, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Insights into spirotetramat-induced thyroid disruption during zebrafish (Danio rerio) larval development: An integrated approach with in vivo, in vitro, and in silico analyses - Fang Jiao; Hua Rong; Yang Zhao; Panfeng Wu; Yaohui Long; Jie Xu; Tao Zhao; Lingxi Han; Jun Wang; Huirong Yang (Environmental Pollution, 2024)

Counteracting effects on ENSO induced by ocean chlorophyll interannual variability and tropical instability wave-scale perturbations in the tropical Pacific - Rong-Hua Zhang; Feng Tian; Qidong Shi; Xiujun Wang; Tongwen Wu (Science China Earth Sciences, 2024)

Association between short-term exposure to ambient air pollution and upper respiratory tract infection in Kunshan - Hua Wang; Guohua Qian; Jian Shi; Wenjie Lu; Yingchao Chen; Kun Fang; Yang Shen; Huan Rong; Xuanhua Huangfu; Yan Feng; Wei Zhang; Kexun Zhang (International Journal of Biometeorology, 2024)

Two birds with one stone: A magneto-optical dual-stimuli-responsive intelligent Pickering emulsion for efficient conversion of glucose to 5-hydroxymethylfurfural - Zhong-Qiu Liu; Jia-Liang Guo; Rong-Hua Liang; Feng-Xiang Wang; Zhan-Ku Li; Yujing Liu; Anguo Ying (Chemical Engineering Journal, 2024)

Advances, challenges, and prospects in microalgal-bacterial symbiosis system treating heavy metal wastewater - Xing-Rui Zhou; Rong Wang; Cong-Cong Tang; Cristiano Varrone; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Chemosphere, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Revealing mechanisms of triclosan on the removal and distribution of nitrogen and phosphorus in microalgal-bacterial symbiosis system - Sheng-Long Chen; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2023)

Nanoscale evidence of zircon-coffinite-xenotime solid solution observed by atom probe tomography - Wenhao Zhao; Bi-Wen Wang; Li-Xin Gu; Xu Tang; Yu Liu; Muhammad Awais; Xiao-Chi Liu; Xian-Hua Li; Rong Hu; Qiu-Li Li (Chemical Geology, 2023)

N, N-bis (2-hydroxyethyl) malonamide based amidoxime functionalized polymer immobilized in biomembranes for highly selective adsorption of uranium(VI) - Yang Li; Ze-Yang Wang; Qi Ren; Feng Zhang; Xu-Xin Li; Qiang Wu; Rong Hua; Ze-Yi Yan; Yun Wang (Chemosphere, 2023)

Detecting endosperm cracks in soaked maize using μCT technology and R-YOLOv7-tiny - Yitao Jiao; Zheng Wang; Yuying Shang; Rong Li; Zhixin Hua; Huaibo Song (Computers and Electronics in Agriculture, 2023)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

Insights into roles of triclosan in microalgal–bacterial symbiosis system treating wastewater - Cong-Cong Tang; Tian-Yang Wang; Rong Wang; Cristiano Varrone; Zixuan Gan; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Bioresource Technology, 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

Characterization of the fragmented mitochondrial genome of domestic pig louse Haematopinus suis (Insecta: Haematopinidae) from China - Rong Li; Yu Nie; Yi-Tian Fu; Yuan-Ping Deng; Wei Wang; Ping-Ping Ma; Guo-Hua Liu (Systematic Parasitology, 2023)

Exploration for cobalt/nitrogen-doped catalyst to creatinine degradation via peroxymonosulfate activation: toxicity evaluation, statistical modeling, and mechanisms study - Jiadi Liu; Yawen Dong; Yu Kang; Qian Kong; Kuaibing Wang; Feifei Mao; Yuanqing Bu; Rong Zhou; Chunyong Zhang; Hua Wu (Environmental Science and Pollution Research, 2023)

Serum levels of IL-6/IL-10/GLDH may be early recognition markers of anti-tuberculosis drugs (ATB) -induced liver injury - Huai-Rong Xiang; Yun Li; Xuan Cheng; Bei He; Hua-Min Li; Qi-Zhi Zhang; Bin Wang; Wen-Xing Peng (Toxicology and Applied Pharmacology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The acceleration on decolorization of azo dyes by magnetic lignin-based materials via enhancing the extracellular electron transfer - Rong-ping Chen; Xin-yuan Wei; Cheng-hao Gan; Bing-cai Cai; Wen-jie Xu; Shareen Niyazi; Quan Wang; Lei Yu; Hui-hua Min; Qiang Yong (Journal of Environmental Management, 2023)

Soybean lecithin and cholesterol-loaded cyclodextrin in combination to enhances the cryosurvival of dairy goat semen - Rong Li; Hubei Zhao; Bowen Li; Siqi Wang; Song Hua (Cryobiology, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Sensitivity of El Niño diversity prediction to parameters in an intermediate coupled model - Haibo Chen; Qiang Wang; Rong-Hua Zhang (Climate Dynamics, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

The role played by tropical cyclones-induced freshwater flux forcing in the upper-ocean responses: A case for Typhoon Yutu (2018) - Shuoni Ye; Rong-Hua Zhang; Hongna Wang (Ocean Modelling, 2023)

Endocrine-disrupting chemicals and autoimmune diseases - Rong-Gui Huang; Xian-Bao Li; Yi-Yu Wang; Hong Wu; Kai-Di Li; Xue Jin; Yu-Jie Du; Hua Wang; Fang-Yi Qian; Bao-Zhu Li (Environmental Research, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Preparation and mechanism of carbon felt supported iron trioxide and zero-valent iron for enhancing anaerobic digestion performance - Zheng-Wei Wang; Chun-Hai WEI; Hua-Rong Yu; Fang-Shu Qu; Hong-Wei Rong; Jun-Guo He; Guang-Li Liu; Xia Huang; Huu Hao Ngo (Chemical Engineering Journal, 2023)

Ectopic over-expression of HaFT-1, a 14-3-3 protein from Haloxylon ammodendron, enhances acquired thermotolerance in transgenic Arabidopsis - Rong Pan; Wenjing Ren; Shuanshuan Liu; Hua Zhang; Xin Deng; Bo Wang (Plant Molecular Biology, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Effects of saline immersion on the physiological alterations of grass goldfish (Carassius auratus) during subsequent recovery in freshwater - Xiaowen Wang; Huijuan Li; Rong Zhang; Lili Liu; Hua Zhu (Fish Physiology and Biochemistry, 2023)

Correction to: Interdecadal wind stress variability over the tropical Pacific causes ENSO diversity in an intermediate coupled model - Junya Hu; Hongna Wang; Chuan Gao; Lu Zhou; Rong-Hua Zhang (Climate Dynamics, 2023)

Proteomics Analysis of Lipid Metabolism and Inflammatory Response in the Liver of Rabbits fed on a High Cholesterol Diet - Jing Wu; Wei-Hua Li; Wei-Rong Wang; Xue-Qin Jin; En-Qi Liu (Cell Biochemistry and Biophysics, 2023)

Chinese version of the auditory verbal learning test: normative study and clinical applications in Chinese-speaking population in Shijiazhuang city - Fang-Ming Dong; Wei Wang; Shang-Zun Guo; Kai Shao; Ya-Xue Song; Ning Han; Yan-Li Jia; Rong-Fang Feng; Jian-Hua Wang (Acta Neurologica Belgica, 2023)

Essential Trace Element Status in Systemic Lupus Erythematosus: a Meta-analysis Based on Case-Control Studies - Hua Wang; Xian-Bao Li; Rong-Gui Huang; Nv-Wei Cao; Hong Wu; Kai-Di Li; Yi-Yu Wang; Bao-Zhu Li (Biological Trace Element Research, 2023)

Transcriptome sequencing and metabolite analysis reveal the single and combined effects of microplastics and di-(2-ethylhexyl) phthalate on Peneaus vannamei - Qiang-Qiang Shi; Xiao-Qian Zhang; Ze-Ming Zhang; Ning-Bo Wang; Hua Liu; Rong-Rong Zhang; Ai-Li Sun; Jiong Chen; Xi-Zhi Shi (Science of The Total Environment, 2023)

In situ mapping of ion distribution profiles and gene expression reveals interactions between hypoxia and Mn2+/Fe2+ availability in barley roots - Feifei Wang; Zhenxiang Zhou; Rong Liu; Yangyang Gu; Song Chen; Rugen Xu; Zhong-Hua Chen; Sergey Shabala (Plant Science, 2023)

Synergistic strategy design of (malonamide-amidoxime) bifunctional branching network crosslinked membrane and application in uranium (VI) resource recovery - Yang Li; Qi Ren; Rong Hua; Hong-Tao Xia; Xu-Xin Li; Ze-Yang Wang; Xuan Fu; Yan-Jun Du; Ze-Yi Yan; Yun Wang (Chemical Engineering Journal, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Salinity interdecadal variability in the western equatorial Pacific and its effects during 1950–2018 - Rong-Hua Zhang; Guanghui Zhou; Hai Zhi; Chuan Gao; Hongna Wang; Licheng Feng (Climate Dynamics, 2023)

Efficient inactivation of the contamination with pathogenic microorganisms by a combination of water spray and plasma-activated air - Li Guo; Pengyu Zhao; Yikang Jia; Tianhui Li; Lingling Huang; Zifeng Wang; Dingxin Liu; Zhanwu Hou; Yizhen Zhao; Lei Zhang; Hua Li; Yu Kong; et al. (Journal of Hazardous Materials, 2023)

Interdecadal wind stress variability over the tropical Pacific causes ENSO diversity in an intermediate coupled model - Junya Hu; Hongna Wang; Chuan Gao; Lu Zhou; Rong-Hua Zhang (Climate Dynamics, 2023)

Effects of long-term grazing exclusion on vegetation structure, soil water holding capacity, carbon and nitrogen sequestration capacity in an alpine meadow on the Tibetan Plateau - Yong-sheng Yang; Fa-wei Zhang; Xian-rong Xie; Jun-bang Wang; Ying-nian Li; Xiao-tao Huang; Hui-ting Li; Hua-kun Zhou (Journal of Mountain Science, 2023)

Effect of super-absorbent polymer on swelling pressure of compacted bentonite infiltrated by alkaline solutions - Zhang-Rong Liu; Wei-Min Ye; He-Hua Zhu; Qiong Wang; Yong-Gui Chen (Applied Clay Science, 2023)

ShuffleNet-Triplet: A lightweight RE-identification network for dairy cows in natural scenes - Yunfei Wang; Xingshi Xu; Zheng Wang; Rong Li; Zhixin Hua; Huaibo Song (Computers and Electronics in Agriculture, 2023)

E3D: An efficient 3D CNN for the recognition of dairy cow's basic motion behavior - Yunfei Wang; Rong Li; Zheng Wang; Zhixin Hua; Yitao Jiao; Yuanchao Duan; Huaibo Song (Computers and Electronics in Agriculture, 2023)

Cumulative effects of temperature on blood pressure during pregnancy: A cohort study of differing effects in three trimesters - Qi Chen; Ya Wang; Hui-Rong Tang; Yuan Wang; Ai-Hua Gu; Xiang-Jun Zhai; Ming-Ming Zheng (Science of The Total Environment, 2023)

An antioxidant lignan glycoside and triterpenoid saponins from the leaves of Synsepalum dulcificum - Xin-Peng Li; Jun-Fei Wang; Rong Huang; Tang-Chang Xu; Si-Si Liu; Qing-Rong Yang; Shao-Hua Wu (Phytochemistry Letters, 2023)

A novel multistage anoxic/aerobic process with sludge regeneration zone (R-MAO) for advanced nitrogen removal from domestic sewage - Lin Cao; Rong Sun; Wenyi Dong; Hongjie Wang; Zhongyi Dai; Xue Wang; Jin Xie; Hua Li (Journal of Environmental Sciences, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

A near-infrared fluorescent probe for monitoring abnormal mitochondrial viscosity in cancer and fatty-liver mice model - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Dong-Hua Chen; Chun-Yan Li (Analytica Chimica Acta, 2023)

Enhanced preservation effects of clove (Syzygium aromaticum) essential oil on the processing of Chinese bacon (preserved meat products) by beta cyclodextrin metal organic frameworks (β-CD-MOFs) - Ying Wang; Yi-Tong Du; Wan-Yu Xue; Liang Wang; Rong Li; Zi-Tao Jiang; Shu-Hua Tang; Jin Tan (Meat Science, 2023)

A ca. 290 Ma hydrothermal calcite in Cambrian dolostone - Zhongwu Lan; Shitou Wu; Fangyue Wang; Bo Liu; Kaibo Shi; Jing Sun; Rong Cao; Xian-Hua Li (Marine and Petroleum Geology, 2023)

Efficient synthesis of PdIr nanocatalysts with controllable surface composition for electrochemical oxidation of methanol - Ce Fu; Pan Wang; Rong-Hua Zhang; Luo-Yi Yan; Zheng Cheng; Xin Zhang; Xin-Wen Zhou (Fuel, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Boosting persulfate activation via paper mill sludge-based biochar for efficient degradation of bisphenol A: Inherent multiple active sites - Zhi-Juan Wang; Yang-Qian Lin; Hua-Jing Zhou; Zi-Lian Liu; Rong-Rong Miao; Xi-Meng Xu; Liang He; Qing-Qing Guan (Chemical Engineering Journal, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

Plastid diversity and chromoplast biogenesis in differently coloured carrots: role of the DcOR3Leu gene - Yu-Min Zhang; Rong-Hua Wu; Lu Wang; Ya-Hui Wang; Hui Liu; Ai-Sheng Xiong; Zhi-Sheng Xu (Planta, 2022)

Homozygous missense mutation in CCDC155 disrupts the transmembrane distribution of CCDC155 and SUN1, resulting in non-obstructive azoospermia and premature ovarian insufficiency in humans - Huan Wu; Xin Zhang; Rong Hua; Yuqian Li; Li Cheng; Kuokuo Li; Yiyuan Liu; Yang Gao; Qunshan Shen; Guanxiong Wang; Mingrong Lv; Yuping Xu; et al. (Human Genetics, 2022)

Naturally-Occurring Antibodies Against Bim are Decreased in Alzheimer’s Disease and Attenuate AD-type Pathology in a Mouse Model - Jie-Ming Jian; Dong-Yu Fan; Ding-Yuan Tian; Yuan Cheng; Pu-Yang Sun; Cheng-Rong Tan; Gui-Hua Zeng; Chen-Yang He; Ye-Ran Wang; Jie Zhu; Xiu-Qing Yao; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2022)

Ambient air pollutants increase the risk of immunoglobulin E–mediated allergic diseases: a systematic review and meta-analysis - Hua Wang; Xian-Bao Li; Xiu-Jie Chu; Nv-Wei Cao; Hong Wu; Rong-Gui Huang; Bao-Zhu Li; Dong-Qing Ye (Environmental Science and Pollution Research, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Three new C 21 steroidal glycosides isolated from Metaplexis japonica and their potential inhibitory effects on tyrosine protein kinases - Xu Wang; Qing-Yun Ma; Chen Liu; Jia Yang; Qing-Tao Lv; Zhen-Hua Tian; Hai-Qiang Jiang; Rong Rong (Natural Product Research, 2022)

A novel alkaloid from the seeds of Sophora alopecuroides L - Zi-Jian Rong; Xiao-Xu Gao; Gao-Sheng Hu; Ting Yan; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2022)

Effects of Chemotherapy on Neuroinflammation, Neuronal Damage, Neurogenesis, and Behavioral Performance in Bone Marrow Transplantation Recipient Mice - Zhong-Yuan Yu; Man-Yu Xu; Zhi-Hao Liu; Gui-Hua Zeng; Huan Fan; Cheng-Rong Tan; Yun-Feng Tu; Xian-Le Bu; Yan-Jiang Wang (Neurotoxicity Research, 2022)

Cassiterite oxygen isotopes in magmatic-hydrothermal systems: in situ microanalysis, fractionation factor, and applications - Yang Li; Sheng He; Rong-Qing Zhang; Xian-Wu Bi; Lian-Jun Feng; Guo-Qiang Tang; Wen-Zhong Wang; Fang Huang; Xian-Hua Li (Mineralium Deposita, 2022)

Polysaccharide Krestin Prevents Alzheimer’s Disease-type Pathology and Cognitive Deficits by Enhancing Monocyte Amyloid-β Processing - Si-Han Chen; Chen-Yang He; Ying-Ying Shen; Gui-Hua Zeng; Ding-Yuan Tian; Yuan Cheng; Man-Yu Xu; Dong-Yu Fan; Cheng-Rong Tan; An-Yu Shi; Xian-Le Bu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

Neoflavonoids from the heartwood of Dalbergia melanoxylon - Meng-fei Wang; Guang-qiang Ma; Feng Shao; Rong-hua Liu; Lan-ying Chen; Yang Liu; Li Yang; Xiao-wei Meng (Natural Product Research, 2022)

Label-Free Quantitative Proteomic Analysis of Three Strains of Viscerotropic Leishmania Isolated from Patients with Different Epidemiological Types of Visceral Leishmaniasis in China - Fu-rong Wei; Chun-hua Gao; Jun-yun Wang; Yue-tao Yang; Feng Shi; Bin Zheng (Acta Parasitologica, 2021)

A new phenol derivative isolated from mangrove-derived fungus Eupenicillium sp. HJ002 - Rong-Qing Mei; Xu-Hua Nong; Bin Wang; Xue-Ping Sun; Guo-Lei Huang; You-Ping Luo; Cai-Juan Zheng; Guang-Ying Chen (Natural Product Research, 2021)

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

Coupling ocean–atmosphere intensity determines ocean chlorophyll-induced SST change in the tropical Pacific - Feng Tian; Rong-Hua Zhang; Xiujun Wang (Climate Dynamics, 2021)

Mesoscale wind stress-SST coupling induced feedback to the ocean in the western coast of South America - Chaoran Cui; Rong-Hua Zhang; Yanzhou Wei; Hongna Wang (Journal of Oceanology and Limnology, 2021)

Growth influence of juvenile golden trout (Oncorhynchus mykiss) in different osmotic conditions: implications for tissue histology, biochemical indicators, and genes transcription involved in GH/IGF system - Baoliang Bi; Yu Gao; Dan Jia; Lingfu Kong; Yanhua Su; Hua Rong; Xiangwei Wu; Xiaowen Wang; Zhuoyong Hu; Qing Hu (Fish Physiology and Biochemistry, 2021)

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Paenibacillus turpanensis sp. nov., isolated from a salt lake of Turpan city in Xinjiang province, north-west China - Li Yang; Hua-Wei Huang; Yun Wang; Ya-Rong Kou; Min Yin; Yu Li; Xue-Qian Wang; Gui-Fang Zhao; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

Phytochemical and antitumor studies on Cynanchum mongolicum (Maxim.) Kom - Yong-Cheng Yang; Yan-Ming Wang; Zi-Jian Rong; Li-Na Hong; Qian Zhang; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2020)

Cathepsin V Mediates the Tazarotene-induced Gene 1-induced Reduction in Invasion in Colorectal Cancer Cells - Chun-Hua Wang; Lu-Kai Wang; Chang-Chieh Wu; Mao-Liang Chen; Chan-Yen Kuo; Rong-Yaun Shyu; Fu-Ming Tsai (Cell Biochemistry and Biophysics, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Identification, functional characterization, and estrogen regulation on gonadotropin-releasing hormone in the spotted scat, Scatophagus argus - Hua-pu Chen; Xue-fan Cui; Yao-rong Wang; Zhi-yuan Li; Chang-xu Tian; Dong-neng Jiang; Chun-Hua Zhu; Yong Zhang; Shui-sheng Li; Guang-li Li (Fish Physiology and Biochemistry, 2020)

A review of progress in coupled ocean-atmosphere model developments for ENSO studies in China - Rong-Hua Zhang; Yongqiang Yu; Zhenya Song; Hong-Li Ren; Youmin Tang; Fangli Qiao; Tongwen Wu; Chuan Gao; Junya Hu; Feng Tian; Yuchao Zhu; Lin Chen; et al. (Journal of Oceanology and Limnology, 2020)

Crosstalk between PKC and MAPK pathway activation in cardiac fibroblasts in a rat model of atrial fibrillation - Wei-hua Guo; Xian Wang; Mei-sheng Shang; Zhe Chen; Qi Guo; Li Li; Hai-ying Wang; Rong-hui Yu; Chang-sheng Ma (Biotechnology Letters, 2020)

High resolution UPLC-MS/MS method for simultaneous separation and determination of six flavonoids from semen cuscutae extract in rat plasma: application to comparative pharmacokinetic studies in normal and kidney-deficient rats - Wei Zhang; Zhi-Tian Fu; Yao Xie; Zhi-Wen Duan; Yu Wang; Rong-Hua Fan (Natural Product Research, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Representing surface wind stress response to mesoscale SST perturbations in western coast of South America using Tikhonov regularization method - Chaoran Cui; Rong-Hua Zhang; Hongna Wang; Yanzhou Wei (Journal of Oceanology and Limnology, 2020)

Toonapolyynes A–D, new polyynes from Toona ciliata - Rong Wang; Fu-Qiang Ni; Jun Sang; Yao Zhang; Jia-Luo Huang; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2020)

Functional Analysis of Sheep POU2F3 Isoforms - Guang-Wei Ma; Yan-Kai Chu; Hua Yang; Xiao-Hong Yan; En-Guang Rong; Hui Li; Ning Wang (Biochemical Genetics, 2020)
POU domain class 2 transcription factor 3 (POU2F3) plays an important role in keratinocyte proliferation and differentiation. Our previous study identified four sheep POU2F3 transcript variants ( POU2F3-1 , POU2F3-2 , POU2F3-3 , and POU2F3-4 ), encoding three POU2F3 protein isoforms (POU2F3-1, POU2F3-2, and POU2F3-3). However, the functional differences among the three POU2F3 isoforms remain unknown. The objective of this study was to determine the tissue expression pattern of the four POU2F3 transcript variants in sheep and to investigate the functional differences in cell proliferation among the three POU2F3 isoforms. Quantitative RT-PCR analysis showed that the four POU2F3 transcripts were ubiquitously expressed in all tested adult sheep tissues, and POU2F3-1 exhibited higher expression level than the other three POU2F3 transcript variants in skin ( P P P P > 0.05). Dual luciferase reporter assays demonstrated that overexpression of any one of the three POU2F3 isoforms significantly inhibited the promoter activities of keratin 14 ( KRT14 ) and matrix metalloproteinase 19 ( MMP19 ) genes ( P KRT14 and MMP19 genes than POU2F3-1 and POU2F3-2 ( P P > 0.05). These results suggest three sheep POU2F3 isoforms have similar functional effects, but to a different extent.

Steroidogenic acute regulatory protein/aldosterone synthase mediates angiotensin II-induced cardiac fibrosis and hypertrophy - Wei-Wei Zhang; Rong-Hua Zheng; Feng Bai; Katelyn Sturdivant; Ning-Ping Wang; Erskine A. James; Himangshu S. Bose; Zhi-Qing Zhao (Molecular Biology Reports, 2020)

Utilization of pre-existing competent and barren quartz veins as hosts to later orogenic gold ores at Huangjindong gold deposit, Jiangnan Orogen, southern China - Liang Zhang; David I. Groves; Li-Qiang Yang; Si-Chen Sun; Roberto F. Weinberg; Jiu-Yi Wang; Sheng-Gang Wu; Lei Gao; Lan-Ling Yuan; Rong-Hua Li (Mineralium Deposita, 2020)

Sky islands as foci for divergence of fig trees and their pollinators in southwest China - Jun‐Yin Deng; Rong‐Hua Fu; Stephen G. Compton; Mei Liu; Qin Wang; Chuan Yuan; Lu‐Shui Zhang; Yan Chen (Molecular Ecology, 2020)
The dynamics of populations and their divergence over time have shaped current levels of biodiversity and in the case of the “sky islands” of mountainous southwest (SW) China have resulted in an area of exceptional botanical diversity. Ficus tikoua is a prostrate fig tree subendemic to the area that displays unique intraspecific diversity, producing figs typical of different pollination modes in different parts of its range. By combining climate models, genetic variation in populations of the tree's obligate fig wasp pollinators and distributions of the different plant phenotypes, we examined how this unusual situation may have developed. We identified three genetically distinct groups of a single Ceratosolen pollinator species that have largely parapatric distributions. The complex topography of the region contributed to genetic divergence among the pollinators by facilitating geographical isolation and providing refugia. Migration along elevations in response to climate oscillations further enhanced genetic differentiation of the three pollinator groups. Their distributions loosely correspond to the distributions of the functionally significant morphological differences in the male figs of their host plants, but postglacial expansion of one group has not been matched by spread of its associated plant phenotype, possibly due to a major river barrier. The results highlight how interplay between the complex topography of the “sky island” complex and climate change has shaped intraspecies differentiation and relationships between the plant and its pollinator. Similar processes may explain the exceptional botanical diversity of SW China.

Factors affecting interdecadal variability of air–sea CO2 fluxes in the tropical Pacific, revealed by an ocean physical–biogeochemical model - Feng Tian; Rong-Hua Zhang; Xiujun Wang (Climate Dynamics, 2019)

Cloud Radiative Feedbacks during the ENSO Cycle Simulated by CAMS-CSM - Lin Chen; Lijuan Hua; Xinyao Rong; Jian Li; Lu Wang; Guo Zhang; Ming Sun; Zi’an Ge (Journal of Meteorological Research, 2019)

Mesoscale SST perturbation-induced impacts on climatological precipitation in the Kuroshio-Oyashio extension region, as revealed by the WRF simulations - Jiaxiang Gao; Rong-Hua Zhang; Hongna Wang (Journal of Oceanology and Limnology, 2019)

Relationship between polymorphisms of the lipid metabolism-related gene PLA2G16 and risk of colorectal cancer in the Chinese population - Xiao-Nv Xie; Jing Yu; Li-Hua Zhang; Zhi-Ying Luo; Dong-Sheng Ouyang; Ling-Jie Zheng; Chun-Yang Wang; Li Yang; Ling Chen; Zhi-Rong Tan (Functional & Integrative Genomics, 2019)

Effects of the arterial radius and the center-line velocity on the conductivity and electrical impedance of pulsatile flow in the human common carotid artery - Hua Shen; Siqi Li; Yu Wang; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2019)

An Assessment of ENSO Stability in CAMS Climate System Model Simulations - Lijuan Hua; Lin Chen; Xinyao Rong; Jian Li; Guo Zhang; Lu Wang (Journal of Meteorological Research, 2019)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

A new benzofuran from the heartwood of Dalbergia latifolia - Rong-Hua Liu; Dan-Yi Mei; Shuai Lin; Ding-Qing Wang; Feng Shao; Lan-Ying Chen; Shan-Liang Guo (Natural Product Research, 2019)

Impact of atmospheric model resolution on simulation of ENSO feedback processes: a coupled model study - Lijuan Hua; Lin Chen; Xinyao Rong; Jingzhi Su; Lu Wang; Tim Li; Yongqiang Yu (Climate Dynamics, 2018)

Altered connectivity patterns among resting state networks in patients with ischemic white matter lesions - Ju-Rong Ding; Xin Ding; Bo Hua; Xingzhong Xiong; Yuqiao Wen; Zhongxiang Ding; Qingsong Wang; Paul Thompson (Brain Imaging and Behavior, 2018)

Regulation of myostatin expression is associated with growth and muscle development in commercial broiler and DMC muscle - Tengfei Dou; Zhengtian Li; Kun Wang; Lixian Liu; Hua Rong; Zhiqiang Xu; Ying Huang; Dahai Gu; Xiaobo Chen; Wenyuan Hu; Jiarong Zhang; Sumei Zhao; et al. (Molecular Biology Reports, 2018)

Soil nutrients in relation to vertical roots distribution in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Jin-ming Hu; Yu-hai Bao; Fei Wang; Xiu-bin He (Journal of Mountain Science, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

De novo transcriptome analysis of an albino mutant Pasphiopedilum pacific shamrock reveals reduced expression of genes related to chloroplast biosynthesis and division - Han Li; Hua Cao; Rong-pei Yu; Zhen Miao; Ji-hua Wang; Su-Ping Qu; Qiang Yuan; Shen-chong Li (Horticulture, Environment, and Biotechnology, 2018)

Sucrose is involved in the regulation of iron deficiency responses in rice (Oryza sativa L.) - Peng-Fei Chen; Lin Chen; Zheng-Rong Jiang; Gao-Peng Wang; Shao-Hua Wang; Yan-Feng Ding (Plant Cell Reports, 2018)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

Linking intraspecific trait variability and spatial patterns of subtropical trees - En-Rong Yan; Liu-Li Zhou; Han Y. H. Chen; Xi-Hua Wang; Xiang-Yu Liu (Oecologia, 2018)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Design, synthesis and anti-cancer evaluation of novel podophyllotoxin derivatives as potent tubulin-targeting agents - Cui Hu; Xiang Zhu; Gu-Hao Wang; Xun Wu; Hong-Wei Han; Gui-Hua Lu; Jin-Liang Qi; Yan-Jun Pang; Rong-Wu Yang; Xiao-Ming Wang; Yong-Hua Yang (Medicinal Chemistry Research, 2018)

A new diaryl 1, 2-diketone from the heartwood of Dalbergia latifolia - Rong-hua Liu; Ding-qing Wang; Pu-zhao Zhang; Feng Shao; Lan-ying Chen; Hui-lian Huang; Shuai Lin (Natural Product Research, 2018)

Mesoscale wind stress–SST coupling in the Kuroshio extension and its effect on the ocean - Yanzhou Wei; Rong-Hua Zhang; Hongna Wang (Journal of Oceanography, 2017)

Improved application of tribenuron-methyl as a chemical hybridizing agent with forchlorfenuron for rapeseed hybrid breeding - Yong-Hong Li; Dian-Rong Li; Wu-Sheng Liang; Jian-Hua Tian; Jian-Chang Li; Hao Wang; Mao-Teng Li; Xu-Peng Guo; Wen-Jie Chen; Zhen-Lan Zhang; Fei Mao; Wei-Guo Zhao (Euphytica, 2017)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

A new pyridine alkaloid from Zingiberis rhizoma - Feng Shao; Ding-qing Wang; Wei Xiong; Pu-zhao Zhang; Guang-qiang Ma; Rong-hua Liu; Xue-lian Yao (Natural Product Research, 2017)

Effect of Co-overexpression of Nisin Key Genes on Nisin Production Improvement in Lactococcus lactis LS01 - Zhi-Jian Ni; Xiao-yuan Zhang; Fei Liu; Miao Wang; Rong-hua Hao; Pei-xue Ling; Xi-Qiang Zhu (Probiotics and Antimicrobial Proteins, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Three-dimensional tomography using high-power induced polarization with the similar central gradient array - Jun-Lu Wang; Pin-Rong Lin; Meng Wang; Dang Li; Jian-Hua Li (Applied Geophysics, 2017)

Particle size distributions and organic-inorganic compositions of suspended particulate matters around the Bohai Strait - Xiao Wang; Changwei Bian; Rong Bi; Wensheng Jiang; Hua Zhang; Xueqing Zhang (Journal of Ocean University of China, 2017)

Tenuigenin promotes the osteogenic differentiation of bone mesenchymal stem cells in vitro and in vivo - Hua-ji Jiang; Xing-gui Tian; Shou-bin Huang; Guo-rong Chen; Min-jun Huang; Yu-hui Chen; Bin Yan; Sheng-fa Li; Jia-jun Tang; Hui-yu Zhao; Liang Wang; Zhong-min Zhang (Cell and Tissue Research, 2017)

Trichoderma harzianum-induced resistance against Fusarium oxysporum involves regulation of nuclear DNA content, cell viability and cell cycle-related genes expression in cucumber roots - Shuang-Chen Chen; Hong-Jiao Zhao; Zhong-Hong Wang; Cai-Xia Zheng; Pu-Yan Zhao; Zhi-Hua Guan; Hai-Yang Qin; Ai-Rong Liu; Xiao-Min Lin; Golam-Jalal Ahammed (European Journal of Plant Pathology, 2017)

Contamination, Fractionation and Biological Risk Related to Metals in Surface Sediments from the Largest Deep Freshwater Lake in China - Hua-Bing Li; Yang-Guang Gu; Rong Wang; Hui-Bin Lu (Archives of Environmental Contamination and Toxicology, 2017)

The LXR ligand GW3965 inhibits Newcastle disease virus infection by affecting cholesterol homeostasis - Xiang-xiang Sheng; Ying-jie Sun; Yuan Zhan; Yu-rong Qu; Hua-xia Wang; Miao Luo; Ying Liao; Xu-sheng Qiu; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2016)

Erratum to: Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Hydrogen sulfide alleviates zinc toxicity by reducing zinc uptake and regulating genes expression of antioxidative enzymes and metallothioneins in roots of the cadmium/zinc hyperaccumulator Solanum nigrum L. - Xiang Liu; Juan Chen; Guang-Hui Wang; Wen-Hua Wang; Zhi-Jun Shen; Mei-Rong Luo; Gui-Feng Gao; Martin Simon; Kabir Ghoto; Hai-Lei Zheng (Plant and Soil, 2016)

Valproic Acid Influences MTNR1A Intracellular Trafficking and Signaling in a β-Arrestin 2-Dependent Manner - Ling-juan Hong; Quan Jiang; Sen Long; Huan Wang; Ling-di Zhang; Yun Tian; Cheng-kun Wang; Jing-jing Cao; Rong-rong Tao; Ji-yun Huang; Mei-hua Liao; Ying-mei Lu; et al. (Molecular Neurobiology, 2016)

Estimation of soil reinforcement by the roots of four post-dam prevailing grass species in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Xiu-bin He; Yu-hai Bao; Qiang Tang; Jin-zhang Gao; Dan-dan Yan; Ming-feng Wang; Yu Li (Journal of Mountain Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Assessment of interannual sea surface salinity variability and its effects on the barrier layer in the equatorial Pacific using BNU-ESM - Hai Zhi; Rong-Hua Zhang; Fei Zheng; Pengfei Lin; Lanning Wang; Peng Yu (Advances in Atmospheric Sciences, 2016)

Simulation of salinity variability and the related freshwater flux forcing in the tropical Pacific: An evaluation using the Beijing normal university earth system model (BNU-ESM) - Hai Zhi; Rong-Hua Zhang; Pengfei Lin; Lanning Wang (Advances in Atmospheric Sciences, 2015)

Heavy metals in wild marine fish from South China Sea: levels, tissue- and species-specific accumulation and potential risk to humans - Jin-Ling Liu; Xiang-Rong Xu; Zhen-Hua Ding; Jia-Xi Peng; Ming-Hua Jin; You-Shao Wang; Yi-Guo Hong; Wei-Zhong Yue (Ecotoxicology, 2015)

Strategies to prevent and reverse liver fibrosis in humans and laboratory animals - Rong-Jane Chen; Hsiang-Hua Wu; Ying-Jan Wang (Archives of Toxicology, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Quantitative analysis of the feedback induced by the freshwater flux in the tropical Pacific using CMIP5 - Hai Zhi; Rong-Hua Zhang; Pengfei Lin; Lanning Wang (Advances in Atmospheric Sciences, 2015)

Effects of glucose, insulin and triiodothyroxine on leptin and leptin receptor expression and the effects of leptin on activities of enzymes related to glucose metabolism in grass carp (Ctenopharyngodon idella) hepatocytes - Rong-Hua Lu; Yi Zhou; Xiao-Chen Yuan; Xu-Fang Liang; Liu Fang; Xiao-Li Bai; Min Wang; Yu-Hua Zhao (Fish Physiology and Biochemistry, 2015)

Effects on Pharmacokinetics of Propranolol and Other Factors in Rats After Acute Exposure to High Altitude at 4,010 m - Li Wenbin; Wang Rong; Xie Hua; Zhang Juanhong; Wu Xiaoyu; Jia Zhengping (Cell Biochemistry and Biophysics, 2015)

Evaluation of pedotransfer functions for estimating saturated hydraulic conductivity in coastal salt-affected mud farmland - Rong-Jiang Yao; Jing-Song Yang; Dan-Hua Wu; Fu-Rong Li; Peng Gao; Xiang-Ping Wang (Journal of Soils and Sediments, 2015)

Expression and clinical role of TCTP in epithelial ovarian cancer - Chen Chen; Yan Deng; Minhui Hua; Qinghua Xi; Rong Liu; Shuyun Yang; Jian Liu; Jianxin Zhong; Meilan Tang; Shumin Lu; Zhimei Zhang; Xiao Min; et al. (Journal of Molecular Histology, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Rapid and simultaneous detection of three major diarrhea-causing viruses by multiplex real-time nucleic acid sequence-based amplification - Qiu-Hua Mo; Hai-Bo Wang; Hui-Rong Dai; Ji-Can Lin; Hua Tan; Qi Wang; Ze Yang (Archives of Virology, 2015)

Processes leading to second-year cooling of the 2010–12 La Niña event, diagnosed using GODAS - Licheng Feng; Rong-Hua Zhang; Zhanggui Wang; Xingrong Chen (Advances in Atmospheric Sciences, 2015)

Tree architecture varies with forest succession in evergreen broad-leaved forests in Eastern China - Xiao-Dong Yang; En-Rong Yan; Scott X. Chang; Liang-Jun Da; Xi-Hua Wang (Trees, 2015)

Signals induced by exogenous nitric oxide and their role in controlling brown rot disease caused by Monilinia fructicola in postharvest peach fruit - Jing Ying Shi; Na Liu; Rong Xin Gu; Li Qin Zhu; Chang Zhang; Qing Guo Wang; Zhong Hua Lei; Yun Yun Liu; Ji Yun Ren (Journal of General Plant Pathology, 2015)

Effects of exogenous NO on the growth, mineral nutrient content, antioxidant system, and ATPase activities of Trifolium repens L. plants under cadmium stress - Shi-Liang Liu; Rong-Jie Yang; Ming-Dong Ma; Fang Dan; Yan Zhao; Pan Jiang; Mao-Hua Wang (Acta Physiologiae Plantarum, 2015)

Humanin attenuates Alzheimer-like cognitive deficits and pathological changes induced by amyloid β-peptide in rats - Gao-Shang Chai; Dong-Xiao Duan; Rong-Hong Ma; Jian-Ying Shen; Hong-Lian Li; Zhi-Wei Ma; Yu Luo; Lu Wang; Xin-Hua Qi; Qun Wang; Jian-Zhi Wang; Zelan Wei; et al. (Neuroscience Bulletin, 2014)

Heme Oxygenase-2 Suppress TNF-α and IL6 Expression via TLR4/MyD88-Dependent Signaling Pathway in Mouse Cerebral Vascular Endothelial Cells - Ren-Jin Chen; Hong-Hua Yuan; Teng-Ye Zhang; Zhen-Zhen Wang; An-kang Hu; Lian-Lian Wu; Zhang-Ping Yang; Yong-Jiang Mao; De-Jun Ji; Xiao-Rong Zhu (Molecular Neurobiology, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Effect of two-linked mutations of the FMO3 gene on itopride metabolism in Chinese healthy volunteers - Li-Ping Zhou; Zhi-Rong Tan; Hao Chen; Dong Guo; Yao Chen; Wei-Hua Huang; Lian-Sheng Wang; Guo-Gang Zhang (European Journal of Clinical Pharmacology, 2014)

Identification of a Novel Mutation in the Presenilin 1 Gene in a Chinese Alzheimer’s Disease Family - Bo Deng; Yan Lian; Xin Wang; Fan Zeng; Bin Jiao; Ye-Ran Wang; Chun-Rong Liang; Yu-Hui Liu; Xian-Le Bu; Xiu-Qing Yao; Chi Zhu; Lu Shen; et al. (Neurotoxicity Research, 2014)

Sensitivity of ENSO variability to Pacific freshwater flux adjustment in the Community Earth System Model - Xianbiao Kang; Ronghui Huang; Zhanggui Wang; Rong-Hua Zhang (Advances in Atmospheric Sciences, 2014)

Effect of NeuroD Gene Silencing on the Migration and Invasion of Human Pancreatic Cancer Cells PANC-1 - Yang Wang; Dong Wei Su; Li Gao; Gui Ling Ding; Can Rong Ni; Ming Hua Zhu (Cell Biochemistry and Biophysics, 2014)

Clodronate-superparamagnetic iron oxide-containing liposomes attenuate renal injury in rats with severe acute pancreatitis - Sheng-chun Dang; Yan-hua Zeng; Ping-jiang Wang; Bao-ding Chen; Rong-fang Chen; Arun Kumar Singh; Pankaj Kumar; Shu Feng; Lei Cui; Hao Wang; Jian-xin Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

Interval Q inversion based on zero-offset VSP data and applications - Gu-Lan Zhang; Xi-Ming Wang; Zhen-Hua He; Jun-Xing Cao; Ke-En Li; Jiao-Jun Rong (Applied Geophysics, 2014)

Dynamic QTL and epistasis analysis on seedling root traits in upland cotton - QINGZHI LIANG; PENGBO LI; CHENG HU; HUA HUA; ZHAOHU LI; YIHUA RONG; KUNBO WANG; JINPING HUA (Journal of Genetics, 2014)

Silencing Pax3 by shRNA inhibits the proliferation and differentiation of duck (Anas platyrhynchos) myoblasts - Rong-Ping Zhang; He-He Liu; Hao-Han Wang; Yan Wang; Chun-Chun Han; Liang Li; Hua He; Heng-Yong Xu; Feng Xu; Ji-Wen Wang (Molecular and Cellular Biochemistry, 2014)

The expression and regulation of DFNA5 in human hepatocellular carcinoma DFNA5 in hepatocellular carcinoma - Cong-Jun Wang; Lin Tang; Dong-Wei Shen; Chao Wang; Qiong-Ying Yuan; Wei Gao; Yong-Kun Wang; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Effect of combined treatment with recombinant interleukin-2 and allicin on pancreatic cancer - Cong-Jun Wang; Chao Wang; Jiang Han; Yong-Kun Wang; Lin Tang; Dong-Wei Shen; Yi Zhao; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Determination of Concentration of Methotrexate Enantiomers in Intracellular and Extracellular Fluids of HepG2 Cells by Liquid Chromatography–Tandem Mass Spectrometry - Rong Wang; Lifang Guo; Hua Xie; Juanhong Zhang; Xiaoyun Li; Wenbing Li; Jianfeng Wang; Xiaoyu Wu; Zhengping Jia (Cell Biochemistry and Biophysics, 2013)

Effect of a single-dose rifampin on the pharmacokinetics of pitavastatin in healthy volunteers - Yao Chen; Wei Zhang; Wei-hua Huang; Zhi-rong Tan; Yi-cheng Wang; Xi Huang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2013)

A chloroplast membrane protein LTO1/AtVKOR involving in redox regulation and ROS homeostasis - Ying Lu; Hua-Rong Wang; Han Li; Hao-Ran Cui; Yue-Guang Feng; Xiao-Yun Wang (Plant Cell Reports, 2013)

Musca Domestica Larva Lectin Induces Apoptosis in BEL-7402 Cells Through a Ca2+/JNK-mediated Mitochondrial Pathway - Chun-Ling Wang; Yan Xia; Jian-Zeng Nie; Minghui Zhou; Rong-Ping Zhang; Li-Li Niu; Li-Hua Hou; Xiao-Hong Cao (Cell Biochemistry and Biophysics, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Enhancing production of a 24-membered ring macrolide compound by a marine bacterium using response surface methodology - Hua Chen; Mian-bin Wu; Zheng-jie Chen; Ming-lu Wang; Jian-ping Lin; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Pharmacokinetics Study of Amoxycillin and Clavulanic acid (8:1)-A New Combination in Healthy Chinese Adult Male Volunteers Using the LC–MS/MS Method - Juanhong Zhang; Yinfu Wang; Hua Xie; Rong Wang; Zhengping Jia; Xiandong Men; Liting Xu; Qiang Zhang (Cell Biochemistry and Biophysics, 2013)

Lithium enhances TRAIL-induced apoptosis in human lung carcinoma A549 cells - Yan Lan; Xiufeng Liu; Rong Zhang; Kai Wang; Yao Wang; Zi-Chun Hua (BioMetals, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Model evidence for interdecadal pathway changes in the subtropics and tropics of the South Pacific Ocean - Rong-Hua Zhang; Zhanggui Wang (Advances in Atmospheric Sciences, 2013)

Methods to measure and analyze ciliary beat activity: Ca2+ influx-mediated cilia mechanosensitivity - Wen-Er Li; Weiwei Chen; Yun-Fei Ma; Qing-Rong Tuo; Xiao-Jing Luo; Ting Zhang; Wen-Bo Sai; Jing Liu; Jinhua Shen; Zhi-Gang Liu; Yun-Min Zheng; Yong-Xiao Wang; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

The role of leptin in lipid metabolism in fatty degenerated hepatocytes of the grass carp Ctenopharyngodon idellus - Rong-Hua Lu; Xu-Fang Liang; Min Wang; Yi Zhou; Xiao-Li Bai; Yan He (Fish Physiology and Biochemistry, 2012)

Oxidative Parameters in the Rat Brain of Chronic Mild Stress Model for Depression: Relation to Anhedonia-Like Responses - Chao Wang; He-ming Wu; Xiao-rong Jing; Qiang Meng; Bei Liu; Hua Zhang; Guo-dong Gao (The Journal of Membrane Biology, 2012)

Domestication and geographic origin of O ryza sativa in C hina: insights from multilocus analysis of nucleotide variation of O . sativa and O . rufipogon - Xin Wei; Wei‐Hua Qiao; You‐Tao Chen; Rong‐Sheng Wang; Li‐Rong Cao; Wan‐Xia Zhang; Nan‐Nan Yuan; Zi‐Chao Li; Han‐Lai Zeng; Qing‐Wen Yang (Molecular Ecology, 2012)
Previous studies have indicated that C hina is one of the domestication centres of A sian cultivated rice ( O ryza sativa ), and common wild rice ( O . rufipogon ) is the progenitor of O . sativa . However, the number of domestication times and the geographic origin of A sian cultivated rice in C hina are still under debate. In this study, 100 accessions of A sian cultivated rice and 111 accessions of common wild rice in C hina were selected to examine the relationship between O . sativa and O . rufipogon and thereby infer the domestication and evolution of O . sativa in C hina through sequence analyses of six gene regions, trn C ‐ycf6 in chloroplast genomes, cox3 in mitochondrial genomes and ITS , E hd1 , W axy , H d1 in nuclear genomes. The results indicated that the two subspecies of O . sativa (indica and japonica) were domesticated independently from different populations of O . rufipogon with gene flow occurring later from japonica to indica; S outhern C hina was the genetic diversity centre of O . rufipogon , and the P earl R iver basin near the T ropic of C ancer was the domestication centre of O . sativa in C hina.

MicroRNA profiles and their control of male gametophyte development in rice - Hua Peng; Jun Chun; Tao-bo Ai; Yong-ao Tong; Rong Zhang; Ming-ming Zhao; Fang Chen; Sheng-hua Wang (Plant Molecular Biology, 2012)

Modulation of El Niño-Southern Oscillation by freshwater flux and salinity variability in the tropical Pacific - Rong-Hua Zhang; Fei Zheng; Jieshun Zhu; Yuhua Pei; Quanan Zheng; Zhanggui Wang (Advances in Atmospheric Sciences, 2012)

Possible novel roles of poly(rC)-binding protein 1 in SH-SY5Y neurocytes: an analysis using a dynamic Bayesian network - Li-Rong Huo; Jian-Tao Liang; Jun-Hua Zou; Lan-Ying Wang; Qi Li; Xiao-Min Wang (Neuroscience Bulletin, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Bioaccessibility and Risk Assessment of Cadmium from Uncooked Rice Using an In Vitro Digestion Model - Lin-Sheng Yang; Xiu-Wu Zhang; Yong-Hua Li; Hai-Rong Li; Ying Wang; Wu-Yi Wang (Biological Trace Element Research, 2012)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Trigonella arcuata-associated rhizobia—an Ensifer (Sinorhizobium) meliloti population adapted to a desert environment - Yu Rong He; Jing Yu Wang; En Tao Wang; Gu Feng; Yue Li Chang; Xin Hua Sui; Wen Xin Chen (Plant and Soil, 2011)

Cloning and functions analysis of a pyruvate dehydrogenase kinase in Brassica napus - Rong-Jun Li; Zhi-Yong Hu; Hua-Shan Zhang; Gao-Miao Zhan; Han-Zhong Wang; Wei Hua (Plant Cell Reports, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Serum complement C3 has a stronger association with insulin resistance than high sensitive C-reactive protein in non-diabetic Chinese - Bangqiong Wang; Qifu Li; Yuanjuan Jiang; Zhoujun Liu; Li Zhong; Rong Luo; Qingfeng Cheng; Hua Qing (Inflammation Research, 2011)

Analysis of the antibodies anti-Toxoplasma gondii by ELISA based on two diagnostic antigens: rSAG1 and rBAG1 - Min Liu; Tao Wang; Hua Li; Ju-Ying Li; Han Zhong; Chang-Zan Tan; De-Cheng Huang; Liang Zhao; Xiao-Guang Chen; Zhao-Rong Lun (Acta Parasitologica, 2011)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. Previous studies have demonstrated that antibodies to Toxoplasma gondii infection are associated with an increased risk of schizophrenia. The objective of this study was to analyze anti-T. gondii antibodies in 477 Chinese schizophrenia patients using an enzyme-linked immunosorbent assay (ELISA) based on recombinant surface antigen 1 (rSAG1), recombinant bradyzoite antigen 1 (rBAG1) and the soluble tachyzoite antigens (STAg) of T. gondii RH strain. Results showed that among the sero-positives (IgG and/or IgM) for T. gondii infection examined in schizophrenia patients, sero-positive samples for rSAG1, rBAG1 and STAg were 20.5% (98/477), 20.5% (98/477) and 23.5% (112/477) respectively, while compared to 210 blood donors, sero-positive (IgG and/or IgM) samples for these antigens (rSAG1, rBAG1 and STAg) were only 5.7% (12/210), 6.2% (13/210) and 5.7% (12/210), respectively. Furthermore, when IgG antibody reaction in the schizophrenia sera was compared with the rBAG1 and rSAG1, results demonstrated that beside the cases which can be detected by both rSAG1 and rBAG1, some sero-positive for T. gondii in schizophrenia sera can only be detected either by rSAG1 or rBAG1. This phenomenon was also observed in the detection of IgM with rSAG1 and rBAG1. 5.9% (28/477) of cases of schizophrenia which are positive for IgG or IgM by rSAG1 are negative for STAg, while 9.2% (44/477) of the schizophrenia cases which are positive for IgG or IgM by rBAG1 are negative for STAg. Although STAg can also be used to diagnose T. gondii infection from schizophrenia patients, it may not actually indicate the infection as some positive samples may be mistakenly considered to be negative. In conclusion, our results demonstrate that the sero-positive rate for T. gondii in the Chinese schizophrenia patients was higher than blood donors. More importantly, our results provide evidence that the combination of rSAG1 and rBAG1 antigens in the diagnosis of T. gondii infection could closely reflect the actual infection of this parasite in schizophrenia patients.

Differential miRNA expression and their target genes between NGX6-positive and negative colon cancer cells - Xiao-Yan Wang; Ming-Hua Wu; Fen Liu; Yu Li; Nan Li; Gui-Yuan Li; Shou-Rong Shen (Molecular and Cellular Biochemistry, 2010)

Seismic analysis of the active character of the Taihang Mountain piedmont fault - Ming-Cai Xu; Jing-Hua Gao; Li-Xin Rong; Guang-Ke Wang; Xiao-Jiang Wang (Applied Geophysics, 2010)

Assessment of effects of climate change and grazing activity on grassland yield in the Three Rivers Headwaters Region of Qinghai–Tibet Plateau, China - Jiang-Wen Fan; Quan-Qin Shao; Ji-Yuan Liu; Jun-Bang Wang; Warwick Harris; Zhuo-Qi Chen; Hua-Ping Zhong; Xin-Liang Xu; Rong-Gao Liu (Environmental Monitoring and Assessment, 2010)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Normal Shear Stress and Vascular Smooth Muscle Cells Modulate Migration of Endothelial Cells Through Histone Deacetylase 6 Activation and Tubulin Acetylation - Yan-Hua Wang; Zhi-Qiang Yan; Ying-Xin Qi; Bin-Bin Cheng; Xiao-Dong Wang; Dan Zhao; Bao-Rong Shen; Zong-Lai Jiang (Annals of Biomedical Engineering, 2010)

Association of TNFAIP3 polymorphism with rheumatic heart disease in Chinese Han population - Rong Hua; Ji-bin Xu; Jiu-cun Wang; Li Zhu; bing Li; Yang Liu; Sheng-dong Huang; Li Jin; Zhi-yun Xu; Xiao-feng Wang (Immunogenetics, 2009)

Temporal patterns of net soil N mineralization and nitrification through secondary succession in the subtropical forests of eastern China - En-Rong Yan; Xi-Hua Wang; Ming Guo; Qiang Zhong; Wu Zhou; Yong-Fu Li (Plant and Soil, 2009)

Ensemble hindcasts of ENSO events over the past 120 years using a large number of ensembles - Fei Zheng; Jiang Zhu; Hui Wang; Rong-Hua Zhang (Advances in Atmospheric Sciences, 2009)

TRANSPARENT TESTA 12 genes from Brassica napus and parental species: cloning, evolution, and differential involvement in yellow seed trait - You-Rong Chai; Bo Lei; Hua-Lei Huang; Jia-Na Li; Jia-Ming Yin; Zhang-Lin Tang; Rui Wang; Li Chen (Molecular Genetics and Genomics, 2009)

Distribution, sources, and potential risk of polycyclic aromatic hydrocarbons (PAHs) in drinking water resources from Henan Province in middle of China - Ying-ge Ma; Jin-ping Cheng; Fei Jiao; Ke-xin Duo; Zheng Rong; Ming Li; Wen-hua Wang (Environmental Monitoring and Assessment, 2008)

Isolation and identification of Sclerotinia stem rot causal pathogen in Arabidopsis thaliana - Ai-rong Wang; Wen-wei Lin; Xiao-ting Chen; Guo-dong Lu; Jie Zhou; Zong-hua Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Dysregulation of CREB binding protein triggers thrombin-induced proliferation of vascular smooth muscle cells - Jing Chen; Hong Jiang; Lin Xu; Li-Hua Zhu; Lang Wang; Hua-Zhi Wen; Xiao-Rong Hu (Molecular and Cellular Biochemistry, 2008)

Characterization of impurities in the bulk drug lisinopril by liquid chromatography/ion trap spectrometry - Pei-xi Zhu; Dan-hua Wang; Cui-rong Sun; Zhi-quan Shen (Journal of Zhejiang University-SCIENCE B, 2008)

Identification of defense-related genes in rice responding to challenge by Rhizoctonia solani - Chang-Jiang Zhao; Ai-Rong Wang; Yu-Jun Shi; Liu-Qing Wang; Wen-De Liu; Zong-Hua Wang; Guo-Dong Lu (Theoretical and Applied Genetics, 2008)

Increased expression of hLRH-1 in human gastric cancer and its implication in tumorigenesis - Shui-Liang Wang; De-Zhu Zheng; Feng-Hua Lan; Xiao-Jun Deng; Jian Zeng; Cheng-Jin Li; Rong Wang; Zhong-Yong Zhu (Molecular and Cellular Biochemistry, 2008)

Cloning, expression, and pharmacological activity of BmK AS, an active peptide from scorpion Buthus martensii Karsch - Jian-Hua Shao; Yue-Qiu Wang; Xiao-Yan Wu; Rui Jiang; Rong Zhang; Chun-Fu Wu; Jing-Hai Zhang (Biotechnology Letters, 2007)

Heregulin protects mesenchymal stem cells from serum deprivation and hypoxia-induced apoptosis - Chun Gui; Jian An Wang; Ai Na He; Tie Long Chen; Rong Hua Luo; Jun Jiang; Xin Yang Hu; Xiao Jie Xie (Molecular and Cellular Biochemistry, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

Cytological and molecular characterization of a novel monogenic dominant GMS in Brassica napus L. - Dao-Jie Wang; Ai-Guang Guo; Dian-Rong Li; Jian-Hua Tian; Fei Huang; Gen-Lou Sun (Plant Cell Reports, 2007)

Berbamine induces apoptosis in human hepatoma cell line SMMC7721 by loss in mitochondrial transmembrane potential and caspase activation - Guan-yu Wang; Jia-wei Zhang; Qing-hua Lü; Rong-zhen Xu; Qing-hua Dong (Journal of Zhejiang University-SCIENCE B, 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)

Shifts in plant nutrient use strategies under secondary forest succession - En-Rong Yan; Xi-Hua Wang; Jian-Jun Huang (Plant and Soil, 2006)

Identification of differentially expressed genes in seeds of two near-isogenic Brassica napus lines with different oil content - Rong-Jun Li; Han-Zhong Wang; Han Mao; Ying-Tang Lu; Wei Hua (Planta, 2006)

Bone marrow mesenchymal stem cell transplantation combined with perindopril treatment attenuates infarction remodelling in a rat model of acute myocardial infarction - Jian-an Wang; Rong-hua Luo; Xing Zhang; Xiao-jie Xie; Xin-yang Hu; Ai-na He; Jie Chen; Jia-hui Li (Journal of Zhejiang University-SCIENCE B, 2006)

Effects of predator-mediated apparent competition on the population dynamics of Tetranychus urticae on apples - Chang-zhong Liu; Lin Yan; Hua-rong Li; Gang Wang (BioControl, 2006)

Rapid Detection of Avian Influenza Virus A and Subtype H5N1 by Single Step Multiplex Reverse Transcription-polymerase Chain Reaction - Hui-Ling Wei; Gui-Rong Bai; Aaron S. Mweene; Ying-Chun Zhou; Yan-Long Cong; Juan Pu; Shuai Wang; Hiroshi Kida; Jin-Hua Liu (Virus Genes, 2006)

Characterization of a novel impurity in bulk drug of lisinopril by multidimensional NMR technique - Dan-hua Wang; Sai-feng Pei; Ming-hua Zhou; Cui-rong Sun; Yuan-jiang Pan (Journal of Zhejiang University-SCIENCE B, 2006)

Genetic Analysis of the Nonstructural (NS) Genes of H9N2 Chicken Influenza Viruses Isolated in China During 1998–2002 - Shuai Wang; Wei-min Shi; Aaron Mweene; Hui-ling Wei; Gui-rong Bai; Jin-hua Liu (Virus Genes, 2005)

The role of CYP2C19 in amitriptyline N-demethylation in Chinese subjects - Zhi-Ping Jiang; Yan Shu; Xiao-Ping Chen; Song-Lin Huang; Rong-Hua Zhu; Wei Wang; Nan He; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)

GSTP1 polymorphisms and gastric cancer in a high-risk Chinese population - Veronica Wendy Setiawan; Zuo-Feng Zhang; Guo-Pei Yu; Qing-Yi Lu; Yong-Liang Li; Ming-Lan Lu; Ming-Rong Wang; Chun Hua Guo; Shun-Zhang Yu; Robert C Kurtz; Chung-Cheng Hsieh (Cancer Causes & Control, 2001)